Effectiveness of cryogenic machining with modified tool holder - Ahmed, Mirghani Ishak; Ismail, Ahmad Faris; Abakr, Yousif Abdalla; Amin, A. K. M. Nurul (Elsevier, 2007)
The present study involves two processes; modification of the tool holder for use with cryogenic cooling system, and implementation of the new design and testing its effect on tool life and product quality. Liquid nitrogen, which is the most suitable fluid for cryogenic machining is used in this work. Two different flow outlets were tested for this modified tool holder. It is found that this modified tool holder for cryogenic cooling is more effective when the coolant out flow is directed away from the cutting edge of the carbide insert. The new modification resulted in the use of smaller amount of nitrogen, higher cutting speeds at heavy depth of cuts and better surface finish. The effect of cryogenic cooling was not pronounced at low speed, small feed and depth of cut. Keywords: Cryogenic machining; Liquid nitrogen; Turning; Tool wear; Heat transfe 15 © 2006 Elsevier B.V. All rights reserved.